No Significant Difference in Depression Rate in Employed and Unemployed in a Pair-Matched Study Design - Mihai, Adriana; Ricean, Alina; Voidazan, Septimiu (Frontiers in Public Health, 2014)
The main objective of this study was to evaluate the differences of depression rate in employed and unemployed persons in the period of financial and economic crisis in Romania, in a pair-matched study design. Method: The cross sectional study uses a pair match design (395 pairs) of two groups of employed and unemployed persons. Other socio-demographic risk factors of depression (gender, age, marital status, residence, ethnicity, educational level and profession) were controlled. The study was done in a historical period of economic crisis, 2009-2010. For the screening of depression we used the Patient Health Questionnaire PHQ – 9. Results: There were no statistical differences (p=0.054) between the depression rates in the employed (17.98%) and unemployed (23.80%) samples. The depression rate in both groups was higher in females, age (51-55), marital status (divorced), living in the rural area, with a low level of education, poverty. Suicidal ideas are more frequent in men, employed persons with low level of education and in unemployed persons with medium level of education. Conclusion: The exposure to short term unemployment status was not associated with change in depression rate in the period of financial and economic crisis in Romania, comparing with controls pair-matched. Unemployment status increases the depression rate only in vulnerable groups such as single or divorced women; and suicidal ideas were associated with the unemployment status (longer than 8 months) in men from rural area with medium level of education.